A seepage-stress coupled analysis of seabed deformation induced by the decomposition of gas hydrate. (2nd December 2011) - Zhao, Zhenwei; Shang, Xinchun
The deformation of seabed considering seepage-stress coupling is analysed using finite element method in this study, the effect of the varying pore pressure on stress field is accounted in the analysis, and the impact of reservoir permeability and the well pressure on the decomposition radius is studied. The changes of mechanical parameters due to hydrate decomposition are achieved by using user defined field subroutine. The results show that vertical and horizontal effective stress of soil in the dissociated area increase significantly while gas hydrates are decomposed by depressurisation. The reservoir permeability and well pressure have significant impact on the decomposition radius. The seabed deformation increases non-linearly with the increasing of the gas hydrate decomposition radius. The maximum vertical displacement reaches 18 m and the maximum horizontal displacement reaches 7.5 m.